Joint optimization method for UAV trajectory and charging/discharging in cell-free mMIMO system on WPT - WANG Qin; NING Luohan; ZHANG Yuxuan; LIU Ying; CAI Yan; ZHAO Haitao (物联网学报)
In cell-free massive multiple-input multiple-output (CF-mMIMO) system, unmanned aerial vehicles (UAV), serving as mobile access point (AP), are increasingly playing a significant role in both communication and task execution. To enhance the endurance of UAV during complex mission executions, the energy transmission and trajectory design for UAV within a cell-free mMIMO system were explored, utilizing wireless power transmission (WPT) as the foundation. With a focus on maintaining communication fairness for users experiencing outages, energy consumption constraints as UAV receive power replenishments from access points throughout their missions were considered. Simultaneously, a joint optimization encompassing the UAV's flight trajectory, charging/discharging time slots, and beamforming configurations were conducted. To address this complex problem, an angle search-based communication-assisted deep Q-network (DQN) algorithm was proposed, facilitating a targeted spatial exploration. Simulation results demonstrate that, while balancing endurance and communication requirements, this algorithm significantly elevates the utilization rate of UAV and enhances communication fairness for interrupted user equipment (UE), ultimately achieving dynamic regional coverage.